2021
DOI: 10.1111/nph.17251
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of rice phytohormone signaling involved in resistance to a piercing‐sucking herbivore

Abstract: Summary Phytohormone, particularly jasmonate (JA) and salicylate (SA) signaling, plays a central role in plant responses to herbivore and pathogen attack. Generally, SA mediates resistance responses against biotrophic pathogens and phloem‐feeding insects, while JA mediates responses against necrotrophic pathogens and chewing insects. The phytohormonal responses mediating rice resistance to a piercing‐sucking herbivore, the brown planthopper (BPH), remains unknown. Here, we combined transcriptome analysis, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 58 publications
5
82
0
Order By: Relevance
“…To deter or poison herbivores or attract their natural enemies, plants have evolved specific and complex mechanisms that are regulated through phytohormone signaling, especially the JA signaling pathway [174]. Although JAs are widely accepted to play a critical role in inducing plant defenses against herbivorous insects, the process through which plants initially activate JA biosynthesis during herbivore encounters remains unclear.…”
Section: Insect Resistancementioning
confidence: 99%
“…To deter or poison herbivores or attract their natural enemies, plants have evolved specific and complex mechanisms that are regulated through phytohormone signaling, especially the JA signaling pathway [174]. Although JAs are widely accepted to play a critical role in inducing plant defenses against herbivorous insects, the process through which plants initially activate JA biosynthesis during herbivore encounters remains unclear.…”
Section: Insect Resistancementioning
confidence: 99%
“…Phytohormones, particularly salicylic acid (SA) and jasmonic acid (JA), play a central role in plant responses to insects (Pieterse et al, 2012). The antagonistic effect between JA and SA was the best studied; however, SA and JA can positively regulate rice defense against BPH, which may depend on the genotype studied (Du et al, 2009;Zhao et al, 2016;He et al, 2020;Xu et al, 2021). In Bph6 plants, SA and JA seem to have synergistic effects on BPH resistance (Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exogenous ABA increases the resistance of rice to BPH by promoting callose deposition, whereas resistant varieties that were treated with fluridone exhibit susceptibility to BPH with reduced callose deposition [ 45 ]. In addition to ABA-mediated signaling pathway, JA-mediated signaling pathway also plays an important role in modulating the resistance of rice to BPH by regulating the production of defensive compounds [ 26 , 31 ]. Thus, JA and ABA signaling pathways, both of which were strengthened in ir JMJ plants compared to WT plants, might contribute to the enhanced resistance of ir JMJ plants to BPH.…”
Section: Discussionmentioning
confidence: 99%
“…To answer this question, we cloned a gene in rice, OsJMJ715 , which contains a JmjC domain and a RING domain, and is induced by gravid BPH female infestation (according to transcriptome data in Xu et al [ 31 ]). By combining molecular biology, biochemistry, and bioassays, we found that OsJMJ715 specifically localized into the nucleus and had ubiquitination activity.…”
Section: Introductionmentioning
confidence: 99%